Li1.2Mn0.55Ni0.15Co0.1O2 (LMR-NMC)-Carbon Coated-LiMnPO4 Blended Electrodes for High Performance Lithium Ion Batteries. Issue 3 (9th February 2018) - Kumar, S. Krishna; Martha, Surendra K.
Abstract : This paper reports significant improvement in energy density of "layered-layered" lithium rich Li1.2 Mn0.55 Ni0.15 Co0.1 O2 (LMR NMC) material by blending with carbon coated LiMnPO4 (CLMP) using mechanical milling. The presence of the CLMP provides interfacial stability under high current (rate) and voltage cycling conditions and thereby improves the energy loss over cycle life in relation to the pristine LMR- NMC. Blend composite electrodes shows stable reversible capacities of >225 mAhg −1 in the voltage window of 2.5 to 4.7 V for more than 200 cycles, and shows improvements in the rate performance, reduction in irreversible capacity loss and Mn dissolution than the pristine LMR-NMC composite electrode. We characterize details of electrochemical performance studies to understand the role of CLMP in improving the interfacial stability at the interface.